Bioengineering a highly productive vaccine strain in embryonated chicken eggs and mammals from a non-pathogenic clade 2·3·4·4 H5N8 strain. Issue 42 (30th September 2019) - An, Se-Hee; Lee, Chung-Young; Hong, Seung-Min; Choi, Jun-Gu; Lee, Youn-Jeong; Jeong, Jei-Hyun; Kim, Jun-Beom; Song, Chang-Seon; Kim, Jae-Hong; Kwon, Hyuk-Joon
Highlights: The titer of a PR8-derived clade 2·3·4·4a H5N8 virus in chicken embryo was very low. H103Y mutation in HA increased virus titer in chicken embryo and thermo-stability. H103Y mutation increased mammalian pathogenicity of the virus as reported. Replacement of PR8 and a prototypic PB2 genes removed the pathogenicity. The safe and productive virus protected chickens from fatal H5N6 virus challenge. Abstract: The clade 2·3·4·4 H5Nx is a highly pathogenic avian influenza (HPAI) virus, which first appeared in China and has spread worldwide since then, including Korea. It is divided into subclades a - d, but the PR8-derived recombinant clade 2·3·4·4 a viruses replicate inefficiently in embryonated chicken eggs (ECEs). High virus titer in ECEs and no mammalian pathogenicity are the most important prerequisites of efficacious and safer vaccine strains against HPAI. In this study, we have synthesized hemagglutinin (HA) and neuraminidase (NA) genes based on the consensus amino acid sequences of the clade 2·3·4·4a and b H5N8 HPAIVs, using the GISAID database. We generated PR8-derived H5N8 recombinant viruses with single point mutations in HA and NA, which are related to efficient replication in ECEs. The H103Y mutation in HA increased mammalian pathogenicity as well as virus titer in ECEs, by 10-fold. We also successfully eradicated mammalian pathogenicity in H103Y-bearing H5N8 recombinant virus by exchanging PB2 genes of PR8 and 01310 (Korean H9N2 vaccine strain). The final optimized H5N8 vaccine strain completely protected against a heterologous clade 2·3·4·4c H5N6 HPAIV in chickens, and induced hemagglutination inhibition (HI) antibody in ducks. However, the antibody titer of ducks showed age-dependent results. Thus, H103Y and 01310PB2 gene have been successfully applied to generate a highly productive, safe, and efficacious clade 2·3·4·4 H5N8 vaccine strain in ECEs.